Frontal sinus septations predict the presence of supraorbital ethmoid cells. (2nd July 2013) - Comer, Brett T.; Kincaid, Nathan W.; Smith, Nathan J.; Wallace, James H.; Kountakis, Stilianos E.
Abstract : Objectives/Hypothesis: This study is undertaken to determine if the presence or absence of multiseptated frontal sinuses is associated with the presence or absence of supraorbital ethmoid cells (SOECs). Study Design: Analysis of prospectively collected data. Methods: Sixty consecutive patients with chronic rhinosinusitis were identified from a prospectively collected database at a tertiary‐referral institution as having full‐sinus computed tomography (CT) scans. Preoperative or initial CT scans of the sinuses were reviewed, specifically identifying the presence or absence of supraorbital ethmoid air cells (SOECS) and frontal sinus multiseptated sections on coronal imaging. Statistical analysis was performed using the chi‐squared test to evaluate any association between the two structural entities. Results: Sixty total patients were identified, for a total of 120 sides. Of the 61 sides with frontal septations, 43 (70%) had SOECs present and 18 (30%) did not. Of the 59 sides without frontal sinus septations, 13 (22%) had SOECs present and 46 (78%) did not (chi squared = 28.3; P = 0.0000001). The difference in the presence of supraorbital ethmoid cells between whites and blacks is also statistically significant (chi squared = 4.23; P = 0.040). Conclusion: The presence of frontal sinus septations appears to be significantly associated with and predictive of the presence of supraorbital ethmoid cells. Thus, identifying frontal sinus septations on sinus CT is implicated with more complex anatomy of the frontal recess. Level of Evidence: NA. Laryngoscope, 123:2090–2093, 2013